Audit Delay and Its Determining Factors - Lulu Ariandi Saputra; Riza Praditha; Siti Nur Reskiyawati Said (www.amertainstitute.com, 2023)
This study aims to analyze the effect of company size and audit committee on audit delay. This study uses a quantitative approach, the type of data used is quantitative data in the form of financial reporting period data, total assets, total audit committee and total board of commissioners. The population in this study are banking companies listed on the Indonesia Stock Exchange. Samples were taken using a purposive technique so that the results obtained were 37 companies with an observation period from 2019-2021. The results of the study show that firm size has a negative and significant effect on audit delay. This means that the larger the size of a company, the faster the company reports its financial condition. Meanwhile, the audit committee has a positive but not significant effect. This means that the size of the audit committee does not really affect company policy in reporting.